Application of multi-criteria decision-making for optimizing the formulation of functional cookies containing different types of resistant starches: A physicochemical, organoleptic, in-vitro and in-vivo study. (1st November 2022) - Falsafi, Seid Reza; Maghsoudlou, Yahya; Aalami, Mehran; Jafari, Seid Mahdi; Raeisi, Mojtaba; Nishinari, Katsuyoshi; Rostamabadi, Hadis
Highlights: Cookie was enriched with various levels of RS3 and RS4. RS-fortified cookies revealed less in-vitro digestibility and remarkably reduced postprandial blood glucose and glycaemic index. TOPSIS successfully determined the best formulation through MCDM approach. Abstract: This research aimed to develop a healthy cookie formulation containing different types of resistant starch, through the application of TOPSIS approach, as a potent feature of MCDM methodologies. Physicochemical investigations reveled that a harder, denser and less sticky dough was produced by the addition of both types of RS. The baking of these doughs resulted in the production of crumblier cookies of less spread ratio, lower porous crumb and whiter surface/crumb. Moreover, in-vitro digestibility of the cookies demonstrated that the baking process can adversely reduce the resistance of RS4 to the enzymolysis reactions. This phenomenon was further corroborated by in-vivo studies where the RS4 enriched cookies were less capable in reducing the postprandial blood glucose. TOPSIS, through successful solving of the multiple criteria decision 9 (alternatives) × 15 (evaluated attributes) matrix suggested that the cookie containing 15% RS is the best alternative in all aspects, possessing acceptable physicochemical/organoleptic attributes, and in-vivo/in-vitro dietary fiber.